The role and assesment of mental and emotional state in patients with arrhythmias - N. G. Neznanov; U. V. Lebedeva; O. Rida; V. B. Petrova; E. I. Palchikova; A. E.K. Yusifzade (Бюллетень сибирской медицины, 2020)
The aim is to study the influence and assessment of mental and emotional states in patients with arrhythmias.Materials and methods. Literature search was performed using the following resources: PubMed, Web of Science, Scopus, as well as in the search system Google Scholar by the key words “psychoarrhythmology”, “neural-cardiac axis”, “psychocardiology”, “arrhythmogenesis”, and “stress-induced arrhythmia”. Articles should be freely available and should represent the most relevant information on the topic. Studies were selected by the largest sample and citation index.Results. In this review of studies on the correlation of psychosocial factors and constitutional features of personality in patients with arrhythmias, the available data on the pathogenesis of cardiac pathology, including the main arrhythmological disorders in nervous excitation caused by negative emotions and stress are presented. The article also reflects the importance of a multidisciplinary approach to risk prediction, potential risk modifiers and approaches to the treatment of cardiac pathology, taking into account the psycho-emotional state of the patient.Conclusion. Reducing the severity of the disease requires a comprehensive approach, in particular, psychodiagnostics, psychocorrection, psychotherapy and psychopharmacotherapy. Further development of this approach to this problem will lead to the creation of new programs for early diagnosis, prevention and treatment of cardiac pathology.